2009
DOI: 10.1007/s10526-009-9218-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and virulence of Lecanicillium lecanii against different aphid species

Abstract: Seven isolates of Lecanicillium lecanii (Zimmermann) Zare & Gams isolated in Spain from infected aphids were characterized using sequences of the Internal Transcribed Spacer (ITS) regions and also based on morphological and physiological characteristics. Four of these seven L. lecanii isolates were selected to assess their virulence against nymphs of Myzus persicae (Sulzer), Nasonovia ribisnigri (Mosley), Macrosiphum euphorbiae (Thomas) and Aphis gossypii Glover. Mortality (%), lethal concentration 50 (LC 50 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…The results demonstrate that this strain has antagonistic effects on aphids, confirming the data already obtained for other strains of the same species or genus (Å sman 2007; Diaz et al 2009;Kim et al 2007;Loureiro and Moino 2006;Roditakis et al 2008;Vu et al 2007). Moreover, this study showed that L. lecanii interacted differently with alate and apterous morphs, with lower Lethal Time (LT) values for alate morphs.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results demonstrate that this strain has antagonistic effects on aphids, confirming the data already obtained for other strains of the same species or genus (Å sman 2007; Diaz et al 2009;Kim et al 2007;Loureiro and Moino 2006;Roditakis et al 2008;Vu et al 2007). Moreover, this study showed that L. lecanii interacted differently with alate and apterous morphs, with lower Lethal Time (LT) values for alate morphs.…”
Section: Discussionsupporting
confidence: 87%
“…Comparison of the lethal effects of different isolates used by other authors (Alavo et al 2001;Askary et al 1998;Å sman 2007;Diaz et al 2009;Fournier and Brodeur 2000;Kim et al 2007;Loureiro and Moino 2006;Safavi et al 2002;Sugimoto et al 2003) is difficult since the mode of distribution of the fungus and experimental conditions vary greatly, and different aphid species and developmental stages were considered. In addition the recent split of the species V. lecanii into different species (Zare and Gams 2001) make the comparison even more difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zare & W. Gams makes a practical interest as a pathogen of arthopods. Literary sources identify an ability of L. lecanii to regulate the number of pest populations in protected ground (Chandler et al, 2005;Diaz et al, 2009;Patogeny..., 2001;Gurulingappa et al, 2011;Scorsetti et al, 2008;Vestergaard et al, 1995). The main advantage of this pathogen lies in the ability of a percutaneous penetration in a host organism, and, hence, a suitability for an application for the control of suctorial pests (aphids, thrips, whitefly and spider mite), which aren't susceptible to contact and intestinal insecticides action.…”
Section: Introductionmentioning
confidence: 99%